Application of Geogrids in Stabilizing Rail Track Substructure - Hussaini, Syed Khaja Karimullah; Sweta, Kumari (Frontiers in Built Environment, 2020)
Large-scale direct shear tests were conducted to assess the performance of geogrid-reinforced ballast-subballast interface followed by triaxial tests to explore the deformation and degradation response of geogrid-reinforced ballast under cyclic loading. While the direct shear testing was performed at applied normal stresses (n) ranging from 20 to 100 kPa and rate of shearing (Sr) from 2.5 to 10.0 mm/min, the cyclic triaxial tests were performed to capture the role of loading frequency (f) ranging from 10 to 40 Hz. Fresh granite ballast and subballast with mean particle size (D50) of 42 and 3.5 mm, and five geogrids having different aperture shapes and sizes (A) were used in this study. The tests results indicated that the behavior of ballast-subballast interface is highly influenced by n and Sr. The friction (φ) and dilation angles (ψ) of unreinforced and geogrid-reinforced ballast-subballast interface is found to reduce from 67.96° to 47.82° and 14.56° to 3.34° with the increase in n and Sr. Marsal’s Breakage (Bg: an index to quantify the breakage of ballast) of unreinforced ballast was found to increase from 2.84 to 6.69 % with the increase in n and Sr. However, the inclusion of geogrids significantly enhanced the friction angle (φ), reduced the extent of dilation angle (ψ), and minimized Bg. The interface efficiency factor () and Bg were found to be a function of A/D50 ratio. Accordingly, a model is developed using multiple linear regression analysis to predict the values of φ, ψ and Bg in terms of the input parameters n, Sr and A/D50 ratio. The results from triaxial tests indicate the deformation and degradation behavior of ballast under cyclic loading conditions to be influenced by the loading frequency (f). The extent of ld and Sv of unreinforced ballast increases from 5.48 to 28.32 mm and 20.13 to 45.40 mm with the increase in f. The value of Bg increased from 4.3 to 11.69 % when the value of f was increased from 10 to 40 Hz. Similarly, the extent of lateral and vertical deformation of ballast was found to be a function of A/D50 ratio.